Prevalence of anemia among pregnant women in their first antenatal care visit in Erbil City: A cross sectional study - Bnar Sardar Yaseen Al-Sardari; Suzan Kh. Younus; Zainab Sardar Yaseen Al-Sardari (Tikrit Journal of Pure Science, 2020)
Background and objectives: Anemia is a common medical disorder during pregnancy with bad consequences on mother and fetus, this study was conducted to determine the prevalence of anemia in pregnant women and correlation of anemia with obstetrical and some demographic characters.